Sentiment Analysis on National Education Policy Change 2020 - et. al., Ritika Biswas, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Examining sentiment is a cycle to recognize the assessment of a text. Individual’s write reviews in web-based media referencing their understanding related to an occasion and are likewise intrigued to know other’s insight on a similar occasion. This categorization can be accomplished utilizing SA. SA extracts structure less text reviews related to an item surveys, an occasion, and so on, from all reviews written by various clients and groups the reviews into various classifications as one or the other positive or negative or impartial assessment. This is otherwise called polarity classification. Individuals these days use emojis in their content progressively to communicate their emotions or reiterate their words. Prior AI methods just include the order of text, emojis or pictures exclusively where emojis with text have consistently been dismissed, accordingly overlooked heaps of feelings. This exploration proposed a calculation and strategy for estimation examination utilizing both text and emojis. In this work, information was investigated utilizing deep learning calculation to find sentiments from tweets utilizing a few highlights like Term frequency inverse document frequency, emoji vocabularies, N-gram and Bag of words.